Defending Democracy: Citizen Participation in Election Monitoring in Post-Authoritarian Indonesia - Dini Suryani (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2015)
The collapse of the authoritarian regime in 1998 has made Indonesia as one of the most democratic country in Southeast Asia. To ensure the quality ofdemocracy, in particular electoral democracy, supervision and monitoring of elections has a veryimportant role. Although the Badan Pengawas Pemilu(Bawaslu) or Election Supervisory Body of Indonesiahas experienced institutional strengthening, this institution has not yet become effective in supervisingand monitoring the elections. Therefore, electionmonitoring conducted by non-state agencies, particularly the citizens become important to complement the performance of Bawaslu. This article aimsto explore how the election monitoring conducted by citizens in the aftermath of post authoritarian era, affect the quality of Indonesian democracy. This article argues that although the citizen participation in monitoring the elections is likely to decline, but thecrowd sourced method that appeared in the 2014election has succeeded in improving the quality of the electoral process as well as defending the democratic regime in Indonesia.